Labor Markets and School-to-Work Transition in Egypt : Diagnostics, Constraints, and Policy Framework - Angel-Urdinola, Diego; Semlali, Amina (World Bank, Washington, DC, 2013)
Analysis in this policy note indicates a rapid deterioration in employment opportunities for young individuals transitioning from school to work in Egypt. Despite substantial improvements in labor market outcomes in recent years (in raising employment and participation and in lowering unemployment), unemployment rates in Egypt remain exceedingly high among youth entering the labor market for the first time. A slow school-to-work transition remains the main reason behind high unemployment rates. Young entrants to the labor market have become more educated than ever before: the share of the working-age-population with university education in Egypt has increased significantly between the years 1998 and 2006 (from 14% to 19% among men and from 9% to 14% among women). However, youth are unable to capitalize the time and resources invested in their education as the labor market is not providing enough good-quality jobs for them. To cope with scarce formal jobs, young-educated workers are opting to work in the informal sector and/or withdraw from the labor force, which is contributing to a deadweight loss of recent investments in education. There are three key factors that seem to explain why school-to-job transition remains low in Egypt: investments in the private sector remain low and capital intensive, new graduates are not equipped with the skills demanded by the private sector, and the public sector still provides incentives for educated individuals (mainly women) to queue for private sector jobs. There are several policy options used in the international context to further enhance the performance of the labor market; such as enhancing employability of new entrants, reforming the technical and vocational training system, and designing targeted programs aiming to boost labor demand.